(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2020)
Purpose: The purpose of this paper is to understand the Role of Personal, Contextual and Psychological Factors on Innovative Work Behavior of Front-Line Employees in service sector.Design/methodology/approach: Existing research emphasized the importance of innovative work behavior of Front-Line Employees in organizational growth and development. Several research paper, thesis, articles etc. have been reviewed to know impact of Personal, Contextual and Psychological factors. This study is based on secondary data.Findings: For service firms, innovation has turned out to be a significant factor inducing their performance and development due to rapid changing environment (Campo et al., 2014; Rodgers, 2007). Competition in the worldwide economy has progressively become knowledge-based and the same holds for service sectors, to achieve business success through smart NWOW (new ways of working) which can be analyzed and measured by performance analysis (Miikka, Maiju Vuolle, Aki J., H. Laihonen, A. Lönnqvist 2015).Limitations/Implications: Employees gave their different viewpoints on Innovative Work Behavior of Front-Line Employees both positive (gain competitive advantage) and negative (there’s chance of conflict of interest due to attitude problem), this paper covers the positive impact. Researches have been conducted on emphasizing a particular factor rather than collective study of all the factors simultaneously such as personal, contextual and psychological.Originality/Value: The paper studies the concept of Innovative work behavior and in relation to front line employees of service firms. It also analyzes the impact of various factors collectively such as personal, contextual and psychological factors on Innovative Work Behavior of front-line employees.